A biomaterials approach to influence stem cell fate in injectable cell-based therapies - Amer, Mahetab H.; Rose, Felicity R.A.J.; Shakesheff, Kevin M.; White, Lisa J. (BioMed Central, 2018)
Background: Numerous stem cell therapies use injection-based administration to deliver high density cell preparations. However, cell retention rates as low as 1% have been observed within days of transplantation. This study investigated the effects of varying administration and formulation parameters of injection-based administration on cell dose recovery and differentiation fate choice of human mesenchymal stem cells.